The Ethics of Freedom and Responsibility in Communication: Building a Public Space with Integrity in the Digital Age - Rahmad Asril Pohan; Rubino Rubino (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Degradation ethics communication in the digital era is manifested in escalation disinformation, speech hatred and misinformation has create crisis integrity room threatening public foundation democracy deliberative and cohesive social research This aim For explore dialectics between freedom and responsibility answer in perspective ethics communication as well as formulate conceptualization room digital public with integrity through approach multi-party. Using method study literature, studies This analyze and synthesize in a way critical various source literature consisting of from book scientific and articles journal. Research results disclose four findings main. First, disinformation, speech hatred and misinformation form something ecosystem pathology mutual communication strengthening and rooted in interactions complex between vulnerability cognitive human, design platform- based algorithm economy attention, and unpreparedness framework adaptive regulation. Second, dialectics freedom and responsibility answer reach its synthesis in perspective ethics Habermas's discourse emphasizes that freedom authentic expression only Possible come true if accompanied by not quite enough answer procedures that allow creation situation ideal speech. Third, development architecture ethics room digital public necessitates synergy tripartite between digital platforms that must reform algorithms and policies moderation content, the country must present regulations precision that protects freedom without become sensor tools, as well as public responsible civilians answer build culture literacy critical from root grass. Fourth, space digital public with integrity characterized by inclusiveness, deliberation equal critical thinking, accountability, and respect to dignity human, which leads to a communication model emancipatory and participatory. Implementation results study This demand an ethical audit platform algorithm, integration critical digital literacy in curriculum education national, as well as strengthening movement check fact based community as form not quite enough answer collective.